The selection of internet service provider during pandemic COVID-19 using Fuzzv AHP and Neutrosophic MCDM approach / Muhammad Syahmi Azizi Mohammad Ghazali, Faizatul Aini Fauzan and Wan Nurul Syahirah Wan Mohd Zin - Mohammad Ghazali, Muhammad Syahmi Azizi; Fauzan, Faizatul Aini; Wan Mohd Zin, Wan Nurul Syahirah (2022)
The increasing internet use has sparked concern worldwide as the pandemic COVID-19 kept spreading. Due to the issues, a few things need to be considered, especially for the stu-dent and the educators. The criteria of the internet provider are also one of the aspects to consider. Previous research has used many methods to determine the best internet provider. This research uses the Fuzzy Analytical Hierarchy Process (AHP) method to determine each chosen criterion’s importance. Using the Fuzzy AHP method makes it more convenient to use triangular fuzzy numbers (TFNs) because of their computational simplicity and effectiveness in representing information in an imprecise environment. From the result of the importance of criteria in Fuzzy AHP, this study will rank and determine the best internet provider among five brands of internet providers using the Neutrosophic Multi-Criteria Decision-Making method (MCDM). In the Neutrosophic MCDM method, the decisions from the decision-maker will be converted to linguistic variables then will be converted to single-valued Neutrosophic numbers. The decision-maker for this study is the students in UiTM, Machang Kelantan, Malaysia, and the chosen location for this study is UiTM Machang, Kelantan, Malaysia. The selected cri-teria for determining the internet provider are cost, service quality, brand image, promotional activities, and accessibility. The internet provider brands are TM(Unifi), Maxis, Celcom, Digi, and TIME. The research objectives are to determine the essential criteria for choosing the inter-net provider using the Fuzzy AHP and select the chosen internet provider using Neutrosophic MCDM. The result obtained gives the most essential criteria is cost, and the least essential crite-ria in choosing the internet provider are promotional activities. For the internet provider brand, the best brand is Digi, and the brand with the lowest rank is the TIME brand.